Attitudes, beliefs, and knowledge regarding medical cannabis among healthcare students in the Republic of Cyprus: a cross-sectional descriptive correlational study - Sokratous, Sokratis; Mpouzika, Meropi; Kaikoushi, Katerina; Alexandrou, George; Karanikola, Maria (Frontiers in Psychiatry, 2023)
Background Although international research-based literature from the last 2 decades seems to favor the use of medical cannabis (MC), there is a lack of evidence concerning healthcare students’ education on MC in the Republic of Cyprus and across the world. Therefore, this study explores healthcare students’ attitudes, beliefs, and knowledge regarding the use of MC. We paid special attention to differences across specific sociodemographic (gender, age, and religion status) and educational (level of study and study field) characteristics. Methods A descriptive cross-sectional study was conducted between November 2019 and March 2020. All active undergraduate and postgraduate healthcare students (nurses, physiotherapists, speech therapists, pharmacists, and occupational therapists; N = 900) studying in public and private universities in the Republic of Cyprus were eligible to participate (final sample: N = 819, response rate = 91%). To collect data on the attitudes, beliefs and knowledge of the participants, we used the Medical Cannabis Questionnaire (MCQ). To analyze the data, we employed the Pearson’s chi-square test for group differences, in addition to assessing the descriptive and inferential statistics. Results Approximately 82.2% believed that MC education should be integrated into the clinical practice requirements. Statistically significant differences were observed between genders in terms of beliefs/risk associated with the use of MC, with males being more likely to believe that there are significant mental-health benefits associated with using ΜC compared to females (84.9% vs. 76.2%, p<0.05). Females were more likely than males to believe that using MC poses serious physical (76.8% vs. 60.6%, p<0.001) and mental-health (77.9% vs. 66%, p<0.001) risks. Moreover, participants who received formal education about MC during their study/training were more prepared to answer patient/client questions about ΜC (p < 0.001). In addition, participants who received formal education had more frequently friends (p < 0.001) or family members who used MC (p < 0.005). Conclusion This study provides useful information for curriculum development, educational changes, and policy decisions related to cannabis use for medical purposes in the Republic of Cyprus. The results showed that the majority of the healthcare students who participated in the study favored MC use. However, the participants reported a lack of knowledge and recommended additional evidence-based research and education to enhance their knowledge about MC use. Therefore, we recommend the implementation of formal education on MC among healthcare students in the Republic of Cyprus during their study and clinical training. Furthermore, it is important to include MC-related theoretical and clinical/laboratory courses during studies and clinical practice.